CONTROL METHOD OF PALM OIL’S RAW MATERIALS SUPPLIES TO GUARANTEE THE QUALITY OF THE PRODUCT - Andira Puspita; Yuni Rahmawati (NAROTAMA UNIVERSITY, Indonesia)
The current economy has grown rapidly, along with the rapidly growing of Science and Technology (IPTEK). So the competition between companies becomes increasingly tight. The increasingly tight competition of the company encourages each company to determine the selection of raw material inventory appropriately so that the company can still exist in order to achieve its desired goals.